Analisis Kesalahan Penulisan Preposisi di- dengan Prefiks di- yang Tidak Sesuai Fungsinya pada Karangan Teks Cerita Ulang (Biografi) Peserta Didik Kelas X SMA Negeri 3 Pemalang Tahun Pelajaran 2020/2021 - Anita Permatasari; Ika Septiana; Mukhlis Mukhlis (Jurnal Kualita Pendidikan, 2021)
This research is motivated by the lack of ability of class X students of SMA Negeri 3 Pemalang in expressing thoughts or ideas into writing, especially in writing between the preposition di- and the prefix di-. Both have the same form, so students find it difficult to distinguish and often make mistakes or make mistakes in writing them. This study is a qualitative descriptive study that aims to describe the types of errors or errors in writing the preposition di- and the prefix di- contained in the biographical texts written by students of class X SMA Negeri 3 Pemalang in the 2020/2021 school year. Data collection in this study used the listening method and note-taking technique by collecting biographical texts written by students for analysis. Then, data analysis was carried out through data reduction, data presentation, and drawing conclusions or verifying research data. The data is classified into two types of errors, namely errors in writing the preposition di- and the writing class of the prefix di-. The technique of presenting the results of data analysis in this study uses the information method, namely the presentation of the results of the analysis using words. Based on the results of data analysis with the discovery of 26 errors in writing the preposition di- and 14 errors in writing the prefix di-, it can be concluded that students do not yet know the function of di- as a preposition and di- as an affix (prefix).